Reducing alcohol-impaired driving in Massachusetts: the Saving Lives Program. - Hingson, R (1996)
OBJECTIVES: The purpose of this study ws to assess whether a community program begun in March 1988 that organized multiple city departments and private citizens could reduce alcohol-impaired driving, related driving risks, and traffic deaths and injuries. METHODS: Trends in fatal crashes and injuries per 100 crashes were compared in Saving Lives Program cities and the rest of Massachusetts from March 1984 through February 1993. In annual roadside surveys conducted at randomly selected locations, safety belt use among occupants of 54577 vehicles and travel speeds of 118442 vehicles were observed. Four statewide telephone surveys (n = 15188) monitored self-reported driving after drinking. RESULTS: In program cities relative to the rest of Massachusetts during the 5 program years in comparison with the previous 5 years, fatal crashes declined 25%, from 178 to 120, and fatal crashes involving alcohol decreased 42%, from 69 to 36. Visible injuries per 100 crashes declined 5%, from 21.1 to 16.6. The proportions of vehicles observed speeding and teenagers who drove after drinking were cut in half. CONCLUSIONS: Interventions organized by multiple city departments and private citizens can reduce driving after drinking, related driving risks, and traffic deaths and injuries.